Method for producing nanoparticle film
Patent Information
- Application Number
- JP2021577692
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-12-10
- Filing Date
- 2021-12-17
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-12-17
AI Technical Summary
【0026】 本発明は、界面活性剤配位子を用いてナノ粒子の表面を修飾し、界面活性剤配位子を溶媒中で電離させることにより、ナノ粒子の表面の帯電量を高め、ナノ粒子膜を電着させるのに必要な駆動電圧を低下させることができる。
Smart Images

Figure 0007640478000003 
Figure 0007640478000004 
Figure 0007640478000005
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of nanomaterials, and in particular to a nanoparticle film, a method for manufacturing a nanoparticle film, and a display panel. [Background technology]
[0002] Nanomaterials are materials whose constituent units are between 1 nanometer and 100 nanometers in size. Because the size is close to the coherence length of electrons, self-organization due to strong coherence significantly changes the properties of nanomaterials. In addition, because the scale of nanomaterials is close to the wavelength of light, they have volume effects, surface effects, quantum size effects, macro quantum tunneling effects, and other unique properties in terms of melting point, magnetism, optics, thermal conductivity, and electrical conductivity, making them of great value in applications in many fields.
[0003] Quantum dots (abbreviated as QD) are typical nanomaterials with characteristics such as small size and high energy conversion efficiency, and are expected to be very importantly applied in the fields of lighting, display technology, solar cells, optical switches, sensors and detection, etc. In addition, quantum dots also have properties such as high brightness, narrow emission angle, adjustable emission color, and stabilization, which are in line with the development trends of ultra-thin, high brightness, wide color gamut, and high color saturation in the display technology field, and therefore have become the new material with the most potential for display technology in recent years.
[0004] The development of patterning technology for nanomaterials such as quantum dots has important value for applications in fields such as light-emitting diodes (LEDs), display technology, solar cells, optical switches, sensors and detection. Currently, the patterning technology for quantum dots mainly includes inkjet printing and photolithography. In the photolithography process, high temperature heating, ultraviolet curing, and rinsing of the developer all affect the stability of nanoparticles. In the printing process, the performance requirements for the printing ink are too high. At present, there is no mature and stable mass-production material system. In addition, the reproducibility of inkjet-printed quantum dots is poor, and the manufacturing time is long. All of the above drawbacks greatly restrict the development and application of quantum dots. As a conventional patterning technology for quantum dots, it is known that the electrodeposition method is used to process quantum dot patterning thin films. However, the charge amount of commercially available quantum dots is low, so the driving voltage required for electrodeposition is high, limiting further applications. Summary of the Invention [Problem to be solved by the invention]
[0005] In view of this, the present invention provides a method for producing a nanoparticle film, which can increase the charge amount of nanoparticles and reduce the driving voltage required to deposit the nanoparticle film, and a nanoparticle film. [Means for solving the problem]
[0006] The present invention relates to providing a nanoparticle solution comprising a solvent and nanoparticles dispersed in the solvent, the nanoparticles having surfactant ligands attached to their surfaces; forming the nanoparticle solution into a nanoparticle film by electrodeposition.
[0007] In one embodiment, the solvent is a non-polar solvent and the concentration of the surfactant ligand is greater than the critical micelle concentration.
[0008] In one embodiment, the mass ratio of the surfactant ligand to the nanoparticles is from 1% to 50%.
[0009] In one embodiment, the step of forming the nanoparticle solution into a nanoparticle film by electrodeposition comprises: providing an electrode for immersion in the nanoparticle solution; applying a driving voltage of 50V to 150V to the electrodes to deposit the nanoparticle solution onto the electrodes to form the nanoparticle film.
[0010] In one embodiment, the solvent is a polar solvent, and the mass ratio of the surfactant ligand to the nanoparticles is 1% to 50%.
[0011] In one embodiment, the mass ratio of the surfactant ligand to the nanoparticles is 1% to 5%.
[0012] In one embodiment, the step of forming the nanoparticle solution into a nanoparticle film by electrodeposition comprises: providing an electrode for immersion in the nanoparticle solution; applying a driving voltage of 1V to 10V to the electrodes to deposit the nanoparticle solution onto the electrodes to form the nanoparticle film.
[0013] In one embodiment, the step of providing the nanoparticle solution comprises: Providing an initial nanoparticle having an initial ligand bound to its surface; mixing the initial nanoparticles with a surfactant to effect a ligand exchange reaction to obtain nanoparticles having surfactant ligands bound to their surfaces; and dissolving the nanoparticles having surfactant ligands attached to their surfaces in a solvent to form a nanoparticle solution.
[0014] In one embodiment, the step of providing the nanoparticle solution comprises: and dissolving the initial nanoparticles and the surfactant in a solvent to obtain nanoparticles having surfactant ligands attached to their surfaces to form a nanoparticle solution.
[0015] In one embodiment, the nanoparticles are quantum dots.
[0016] In one embodiment, the surfactant ligand is at least one selected from an organic sulfonate surfactant, a metal soap surfactant, an organic amine surfactant, an organic phosphate surfactant, and a phosphoric acid ester surfactant.
[0017] The present invention further provides a nanoparticle membrane comprising nanoparticles having surfactant ligands attached to their surfaces.
[0018] In one embodiment, the mass ratio of the surfactant ligand to the nanoparticles is from 1% to 50%.
[0019] In one embodiment, the mass ratio of the surfactant ligand to the nanoparticles is 1% to 5%.
[0020] In one embodiment, the nanoparticles are quantum dots.
[0021] In one embodiment, the surfactant ligand is at least one selected from an organic sulfonate surfactant, a metal soap surfactant, an organic amine surfactant, an organic phosphate surfactant, and a phosphoric acid ester surfactant.
[0022] The present invention further provides a display panel comprising the nanoparticle film according to any one of the above claims, wherein said nanoparticles are quantum dots.
[0023] In one embodiment, the mass ratio of the surfactant ligands to the nanoparticles is 1% to 50%.
[0024] In one embodiment of the display panel, the mass ratio of the surfactant ligands to the nanoparticles is 1% to 5%.
[0025] In one embodiment of the display panel, the nanoparticles are quantum dots. Effect of the Invention
[0026] The present invention modifies the surface of a nanoparticle with a surfactant ligand and ionizes the surfactant ligand in a solvent, thereby increasing the amount of charge on the surface of the nanoparticle and reducing the driving voltage required to electrodeposit a nanoparticle film. [Brief description of the drawings]
[0027] In order to more clearly describe the technical means in the present invention, the drawings necessary to be used in the following description of the embodiments are briefly introduced, and the drawings in the following description are only some examples of the present invention, and it is obvious that those skilled in the art can also derive other drawings from these drawings without creative efforts. [Figure 1] FIG. 1 is a flow chart of a method for producing a nanoparticle film of the present invention. [Diagram 2] FIG. 2 is a flowchart of the method for producing a nanoparticle film according to the first embodiment of the present invention. [Diagram 3] FIG. 3 is a flow chart of a method for producing a nanoparticle film according to a second embodiment of the present invention. [Figure 4] FIG. 4 is a schematic diagram of electrodes when no voltage is applied in the production of a nanoparticle film of the present invention. [Diagram 5] FIG. 5 is a schematic diagram showing how quantum dots are deposited on an electrode when a voltage is applied in the production of a nanoparticle film of the present invention. [Figure 6] FIG. 6 is a structural schematic diagram of a first embodiment of a display panel of the present invention. [Figure 7] FIG. 7 is a structural schematic diagram of a second embodiment of a display panel of the present invention. [Figure 8] FIG. 8 is a structural schematic diagram of a third embodiment of a display panel of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] Hereinafter, the technical means of the present invention will be described clearly and completely with reference to the drawings in the embodiments of the present invention. It is clear that the described embodiments are not all the embodiments, but are only some of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative efforts are all within the protection scope of the present invention.
[0029] In the present invention, unless otherwise clearly specified and limited, the first feature being "above" or "below" the second feature may include that the first feature and the second feature are directly connected, or that the first feature and the second feature are not directly connected but are in contact with each other through other features between them. Furthermore, the first feature being "above", "above" and "on the upper surface" of the second feature may include that the first feature is directly above and diagonally above the second feature, or may simply indicate that the height of the first feature is higher than that of the second feature. The first feature being "below", "below" and "on the lower surface" of the second feature may include that the first feature is directly below and diagonally below the second feature, or may simply indicate that the height of the first feature is lower than that of the second feature. In addition, the terms "first" and "second" are merely for descriptive purposes and should not be understood to indicate or suggest relative importance or imply the number of technical features shown. Thus, a feature defined by "first" and "second" may expressly or imply that it includes one or more features.
[0030] The present invention provides a method for producing a nanoparticle film. Referring to FIG. 1, the method for producing a nanoparticle film includes steps 101 and 102.
[0031] Step 101: Providing a nanoparticle solution including a solvent and nanoparticles dispersed in the solvent, the nanoparticles having surfactant ligands attached to their surfaces.
[0032] In step 101, the solvent may be a polar solvent or a non-polar solvent. In order to facilitate the subsequent volatilization film formation, the solvent may be a colorless, transparent, low-boiling, and easily volatile organic solvent or inorganic solvent.
[0033] The nanoparticles for producing the nanoparticle film may be selected from nanoparticles such as nonmetallic inorganic nanoparticles, metal nanoparticles, colloidal nanosheets, and colloidal nanorods. If desired, the nanoparticles may be quantum dots. The quantum dots according to the present invention may be selected from core-shell quantum dots. The light-emitting core of the core-shell quantum dot may be selected from one of ZnCdSe2, InP, Cd2Sse, CdSe, Cd2SeTe, and InAs, and the inorganic protective shell layer may be selected from at least one of CdS, ZnSe, ZnCdS2, ZnS, and ZnO, and the quantum dot material may be selected from highly stable composite quantum dots such as hydrogel-supported quantum dot structures and CdSe-SiO2, or may be perovskite quantum dots. It should be understood that the quantum dot material used in the present invention is not limited to the above. Hereinafter, quantum dots will be described as an example of the nanoparticles of the present invention, but the nanoparticles of the present invention are not limited to quantum dots.
[0034] The surfactant may be selected from cationic surfactants, anionic surfactants, amphoteric surfactants, and some nonionic surfactants that are easily ionized in a solvent. The cationic surfactant may be an amine salt type cationic surfactant such as a primary amine salt, a secondary amine salt, or a tertiary amine salt surfactant, a quaternary ammonium salt type cationic surfactant, a heterocyclic type cationic surfactant containing a nitrogen-containing morpholine ring, a pyridine ring, an imidazole ring, a piperazine ring, or a quinoline ring, or an onium salt type cationic surfactant such as an onium salt, a sulfonium salt, an iodonium, or an onium compound. Specifically, the cationic surfactant may be, for example, an alkyl trimethyl ammonium chloride, an alkyl benzyl dimethyl ammonium chloride, a dialkyl dimethyl ammonium chloride, a trimethyl dodecyl ammonium chloride, a cetyl pyridinium chloride or bromide, a dodecyl pyridinium bromide, a cetyl pyridinium chloride, or a cetyl pyridinium bromide.
[0035] Anionic surfactants include four types: carboxylates, sulfonates, sulfates, and phosphates. Carboxylate-type anionic surfactants include potassium, sodium, ammonium, and triethanolammonium salts of higher fatty acids, such as alkali metal soaps (monovalent soaps), alkaline earth metal soaps (divalent soaps), and organic amine soaps (triethanolamine soaps), as well as metal soap-based surfactants such as naphthoates or stearates of metals such as cobalt, aluminum, and iron. Sulfonate-type anionic surfactants include alkylbenzenesulfonates, α-olefinsulfonates, alkylsulfonates, α-sulfomonocarboxylates, fatty acid sulfoalkyl esters, succinate sulfonates, alkylnaphthalenesulfonates, petroleum sulfonates, ligninsulfonates, and alkylglyceryl ether sulfonates, such as dioctyl sodium sulfosuccinate, calcium dodecylbenzenesulfonate, sodium dodecylbenzenesulfonate, and barium dinonylnaphthalenesulfonate. The sulfate anionic surfactants include two types: fatty alcohol sulfate (also called primary alkyl sulfate) and secondary alkyl sulfate. The alkyl phosphate salts include alkyl mono- and di-ester phosphate salts, as well as fatty alcohol polyoxyethylene ether mono- and di-ester phosphate salts and alkylphenol polyoxyethylene ether mono- and di-ester phosphate salts.
[0036] Examples of amphoteric surfactants include lecithin amphoteric surfactants, amino acid amphoteric surfactants, and betaine amphoteric surfactants. Amino acid amphoteric surfactants and betaine amphoteric surfactants have an anion moiety that is mainly a carboxylate and a cation moiety that is a quaternary ammonium salt or an amine salt, with those made of an amine salt being amino acid type and those made of a quaternary ammonium salt being betaine type. For example, examples of amino acid amphoteric surfactants include octadecyl dihydroxyethylamine oxide, octadecyl amidopropylamine oxide, and lauramidopropylamine oxide. Examples of betaine amphoteric surfactants include dodecyl ethoxy sulfobetaine, dodecyl hydroxypropyl sulfobetaine, dodecyl sulfopropyl betaine, tetradecane amidopropyl hydroxypropyl sulfobetaine, and decyl hydroxypropyl sulfobetaine.
[0037] The nonionic surfactant may be an N-vinylpyrrolidone polymer (polyvinylpyrrolidone) or the like.
[0038] Optionally, in some embodiments, the surfactant may be at least one of organic sulfonate surfactants such as calcium dodecylbenzenesulfonate, sodium dodecylbenzenesulfonate, and barium dinonylnaphthalenesulfonate, which have strong binding strength with quantum dots; metal soap surfactants such as naphthalene salts and stearates of metals such as cobalt, aluminum, and iron; organic amine surfactants such as octadecyldihydroxyethylamine oxide; N-vinylpyrrolidone polymers; and organic phosphate and phosphoric acid ester surfactants.
[0039] The surfactant used in the present invention is ionizable in a solvent and has a binding force with the surface of the quantum dot. In order to ensure the binding force between the quantum dot and the surfactant, if desired, when the surface of the quantum dot is an acidic group, a basic surfactant is selected, and when the surface of the quantum dot is a basic group, an acidic surfactant is selected. Note that the quantum dot surface may contain only surfactant ligands, or may contain other ligands, such as oleic acid, thiol, carboxylic acid, organic amine ligand, etc.
[0040] Conventional ligands such as oleic acid, thiol, carboxylic acid, and organic amines bonded to the surface of quantum dots are difficult to dissociate in a solvent, or the degree of dissociation is low, resulting in a low charge amount of the quantum dots in the quantum dot solution. When a quantum dot thin film is manufactured by electrodeposition, the charge amount of the quantum dots is too low, so the driving voltage required to deposit the quantum dots to form a film is too high. In the present invention, the surface of the quantum dots is charged by modifying the surface of the quantum dots with a surfactant ligand that has a high degree of dissociation in a solution, and the charge amount of the quantum dots is increased by increasing the degree of ionization of the ligand, thereby making it possible to reduce the driving voltage when forming a quantum dot thin film by electrodeposition.
[0041] The method of modifying quantum dots with surfactant ligands of the present invention is applicable to polar and non-polar solution systems, which will be described below.
[0042] When the solvent is non-polar, the concentration of surfactant ligands in the solution becomes higher than the critical micelle concentration (CMC) to form reverse micelles. When the surfactant exceeds a certain concentration in the solution, it will form colloidal aggregates, i.e., micelles, by associating with single ions or molecules. The concentration at which the solution suddenly changes its properties, i.e., when micelles begin to form, is called the critical micelle concentration. Surfactants are dissolved in non-polar organic solvents, and when the concentration exceeds the critical micelle concentration, the micelles formed in the organic solvent are called reversed micelles or reversed-phase micelles. The non-polar solvent may be an organic solvent such as n-octane, isooctane, or n-octanol. Typically, organic solvents such as n-octane, isooctane, or n-octanol can be used as the organic phase of the reversed micelle system. In non-polar solution systems, the ligands commonly used in quantum dots, such as oleic acid, thiols, carboxylic acids, and organic amines, are not easily ionized. In addition, when the surface of the quantum dot is modified with a surfactant-based ligand such as sodium dodecylbenzenesulfonate or a phosphate-based surfactant, and the concentration of the surfactant exceeds a critical concentration, i.e., the critical micelle concentration, multiple surfactant molecules aggregate to form reverse micelles. The surfactant forms a polar core with the polar portion facing inward, and the polar core may contain a small amount of water or other impurities. The tail of the non-polar surfactant faces outward into the non-polar solvent, dissolving the quantum dot with the ligand bound to the surface in the non-polar solvent. A surfactant that does not form a reverse micelle can exist in the polar core of the reverse micelle, and can be ionized at the polar site in the polar core, and the ionized surfactant group capable of interacting with the surface of the quantum dot can be bound to the surface of the quantum dot, thereby adsorbing the ionized surfactant to the surface of the quantum dot and charging the quantum dot. In addition, the higher the surfactant concentration, the more reverse micelles are formed, and the more ionized the surfactant, the more charged surfactant can be adsorbed to the surface of the quantum dot, and the greater the charge of the quantum dot.If the shell of the quantum dot is CdS and the surfactant ligand is sodium dodecylbenzenesulfonate, multiple sodium dodecylbenzenesulfonates form reverse micelles and dissolve in a non-polar solvent. Sodium dodecylbenzenesulfonates that do not form reverse micelles ionize at the polar nucleus of the reverse micelles. The ionization of the surfactant is a dynamic exchange reaction, and during the dynamic exchange, for example, cations Na. + Polar ions such as these are ionized at the polar sites of the polar nuclei and captured by the polar nuclei, and ionized nonpolar ions such as dodecylbenzenesulfonate ions, which have a strong bonding action with the surface of the quantum dot, are adsorbed onto the surface of the quantum dot, and the dodecylbenzenesulfonate ions are ionized and become negatively charged, thereby increasing the amount of charge on the quantum dot surface.
[0043] In a non-polar solvent, the mass ratio of the surfactant to the quantum dots may be 1% to 50% in order to increase the charge on the quantum dot surface. As the surfactant becomes higher, the charge on the quantum dots also increases. However, when considering the effect on the photoelectric properties of the quantum dots at the same time, different types and contents of ligands are required for different quantum dots. If the amount of surfactant ligand is too large, it may affect the photoelectric properties of the quantum dots, so the mass ratio of the surfactant to the quantum dots is 50%. Preferably, the mass ratio of the surfactant to the quantum dots may be 20% to 50%.
[0044] It has been experimentally confirmed that when the mass ratio of the surfactant to the quantum dots is 1% to 50%, the driving voltage for electrodepositing the quantum dot film can be reduced to 50V to 192V, and when the mass ratio of the surfactant to the quantum dots is 20% to 50%, the driving voltage for electrodepositing the quantum dot film in a non-polar solvent can be reduced to 50V to 150V.
[0045] The nanoparticle film of the present invention can also be formed in a polar solution system. The polar solvent may be selected from ethanol, water, or propylene glycol monomethyl ether acetate (PGMEA), etc. For example, ligands commonly used in quantum dots, such as oleic acid, thiol, carboxylic acid, and organic amine, can be ionized in a polar solution, but the charge of the quantum dots is low due to the low degree of ionization and the low content of ligand. Therefore, even in a polar solution system, a surfactant can be used to modify the quantum dots, and the surfactant is directly ionized in a polar solvent, the degree of ionization is much higher than that of conventional quantum dot ligands, and the charge of the quantum dots is high. Since the ionization degree of the surfactant in a polar solution is high, the concentration of the surfactant does not need to be too high compared to a non-polar solution system, and the mass ratio of the surfactant to the quantum dots may be 1% to 5%. Of course, in order to further increase the charge, the mass ratio of the surfactant to the quantum dots can be 1% to 50%.
[0046] It has been experimentally confirmed that when the mass ratio of the surfactant to the quantum dots is 1% to 50%, the driving voltage for electrodepositing the quantum dot film can be reduced to 1V to 48V, and when the mass ratio of the surfactant to the quantum dots is 20% to 50%, the driving voltage for electrodepositing the quantum dot film can be reduced to 1V to 10V.
[0047] Commercially available quantum dot materials have initial ligands on their surfaces so that they can be easily dispersed in a solvent. Thus, nanoparticles with surfactant ligands bound to their surfaces can be formed by carrying out a ligand exchange reaction with the initial ligands on the surface of the quantum dots using a surfactant that has a strong binding force with the quantum dots, such as a phosphate surfactant, or by directly adding a surfactant to the quantum dot solution instead of the initial ligands. The initial ligands on the surface of the quantum dots can be completely replaced with surfactant ligands using a ligand exchange reaction. Note that complete replacement here means that the presence of the initial ligands is not detected within the instrument detection range, and is considered to be complete replacement. In addition, by directly adding a surfactant to the quantum dot solution instead of the initial ligands, the replacement rate of the surfactant ligands on the surface of the resulting quantum dots is low, but the requirements of the present invention can be met. For example, a phosphate surfactant has a strong binding force with quantum dots such as CdS / ZnS. Taking advantage of this, in the core-shell quantum dot, for example, when the shell material is CdS / ZnS, the initial ligand is a carboxyl group or an amine-based ligand, and the initial ligand has a mercapto group at one end and a carboxyl group and an amino group at the other end. The surface of the quantum dot is bonded to the initial ligand through the interaction between the S atom and the mercapto group of the initial ligand, and the carboxyl group and the amino group at the end are released. However, since the binding force of the phosphate ester-based surfactant to the S atom is stronger than that between the mercapto group and the S atom, it binds to the surface of the quantum dot in place of the initial ligand by taking away the binding site between the S atom of CdS / ZnS and the initial ligand.
[0048] Specifically, the step of providing the nanoparticle solution includes: Providing an initial nanoparticle having an initial ligand bound to its surface; mixing the initial nanoparticles with a surfactant to effect a ligand exchange reaction to obtain nanoparticles having surfactant ligands bound to their surfaces; and dissolving the nanoparticles having surfactant ligands attached to their surfaces in a solvent to form a nanoparticle solution.
[0049] Since non-polar solvents have a high requirement for the concentration of surfactant bound to the surface of the nanoparticles in order to form reverse micelles and increase the amount of charge on the surface of the nanoparticles, it is preferable to form nanoparticles having surfactant ligands bound to their surface by a ligand exchange reaction.
[0050] Alternatively, the step of providing the nanoparticle solution may include: The method may also include providing initial nanoparticles and a surfactant, and dissolving the initial nanoparticles and the surfactant in a solvent to obtain nanoparticles and a nanoparticle solution having surfactant ligands attached to their surfaces.
[0051] The initial nanoparticles may have an initial ligand bound to their surface, and the initial nanoparticles with the initial ligand bound to their surface may be commercially available, or the initial nanoparticles may not have an initial ligand bound to their surface, and the initial nanoparticles may be obtained in a laboratory. When the initial nanoparticles have no ligands on their surface, the surfactant binds to the nanoparticle surface through atomic interactions with the surface of the initial nanoparticles. When the initial nanoparticles have ligands on their surface, the atomic binding force between the surfactant and the surface of the initial nanoparticles is greater than the binding force between the surface of the initial nanoparticles and the initial ligands, and the surfactant binds to the surface of the nanoparticles instead of the initial ligands, resulting in nanoparticles with surfactant ligands bound to their surface.
[0052] Because polar solvents have low requirements for the concentration of surfactant bound to the surface of the nanoparticles, it is preferable to add the surfactant directly to the quantum dot solution to form nanoparticles with surfactant ligands bound to their surface, thereby eliminating the ligand exchange reaction and reducing production costs.
[0053] Step 102: The nanoparticle solution is formed into a nanoparticle film by electrodeposition.
[0054] In step 102, specifically, the step of forming the nanoparticle solution into a nanoparticle film by electrodeposition includes: providing an electrode for immersion in the nanoparticle solution; and applying a driving voltage to the electrode to deposit the nanoparticle solution onto the electrode to form a nanoparticle film. The driving voltage can be adjusted according to the polarity and ligand content of the solution system. The electrode can be a metal electrode or a transparent oxide electrode, such as an indium oxide (ITO) electrode.
[0055] The present invention modifies the surface of a nanoparticle with a surfactant ligand and ionizes the surfactant ligand in a solvent, thereby increasing the amount of charge on the surface of the nanoparticle and reducing the driving voltage required to electrodeposit a nanoparticle film.
[0056] This is of great value to the improvement of mass productivity of electrodeposition technology. Different types of surfactant ligands and concentrations of ligands can be selected according to the solvent system. In non-polar solvents, the surfactant forms reverse micelles to form polar sites, promoting the ionization of the surfactant, and one end of the ionized surfactant connects to the surface of the nanoparticles, thereby charging the nanoparticles. The higher the concentration of the surfactant, the more reverse micelles are formed, and the higher the charge of the nanoparticles. In polar solvents, the surfactant can be directly ionized, so that an appropriate surfactant can be directly added to the quantum dot system in the polar solvent, thereby increasing the charge of the quantum dots.
[0057] Referring to FIG. 2, the method for producing a nanoparticle film according to the first embodiment of the present invention includes steps 201 to 205.
[0058] Step 201: Provide initial nanoparticles having initial ligands bound to their surfaces.
[0059] Step 202: The initial nanoparticles are mixed with a surfactant to undergo a ligand exchange reaction, resulting in nanoparticles having surfactant ligands attached to their surfaces.
[0060] Step 203: The nanoparticles having surfactant ligands attached to their surfaces are dissolved in a solvent to form a nanoparticle solution, the concentration of the surfactant ligands in the solution being greater than their critical micelle concentration.
[0061] In step 203, the solvent is a non-polar solvent and the surfactant ligands form reverse micelles on the surface of the nanoparticles to increase the surface charge of the nanoparticles.
[0062] Step 204: Providing an electrode for immersion in the nanoparticle solution.
[0063] Step 205: Apply electricity to the electrodes to deposit the nanoparticles on the electrodes, and dry to form a nanoparticle film. When the mass ratio of the surfactant to the quantum dots is 1% to 50%, the driving voltage is 50V to 192V. If desired, when the mass ratio of the surfactant to the quantum dots is 20% to 50%, the driving voltage may be reduced to 50V to 150V.
[0064] Referring to FIG. 3, the method for producing a nanoparticle film according to the second embodiment of the present invention is used to produce a nanoparticle film in a polar solution system, and includes steps 301 to 303.
[0065] Step 301: Initial nanoparticles and a surfactant are dissolved in a solvent to obtain nanoparticles having surfactant ligands bound to their surfaces and a nanoparticle solution.
[0066] In step 301, the solvent is a polar solvent.
[0067] Step 302: Provide an electrode for immersion in the nanoparticle solution.
[0068] Step 303: Apply electricity to the electrodes to deposit the nanoparticles on the electrodes, and dry to form a nanoparticle film. The driving voltage is 1V-48V when the mass ratio of the surfactant to the quantum dots is 1%-50%. If desired, the driving voltage may be reduced to 1V-10V when the mass ratio of the surfactant to the quantum dots is 20%-50%.
[0069] The method for producing a nanoparticle film of the present invention has been described above using a non-polar solution system and a polar solution system as examples. Note that the method for producing a nanoparticle film of the first and second embodiments of the present invention is applicable to both a non-polar solution system and a polar solution system. EXAMPLES
[0070] Next, the method for producing a nanoparticle film of the present invention will be described with reference to specific examples.
[0071] [Example 1] Core-shell quantum dots CdSe (core) / ZnS (shell) with oleylamine as the initial ligand were mixed with isooctyl alcohol polyoxyethylene phosphate (phosphate ester surfactant) in a mass ratio of 100:1 to undergo a ligand exchange reaction, obtaining quantum dots with isooctyl alcohol polyoxyethylene phosphate ligands bonded to the surface. The mass ratio of the core-shell quantum dots CdSe (core) / ZnS (shell) to isooctyl alcohol polyoxyethylene phosphate refers to the mass ratio of the quantum dots and surfactant, not including the mass of the initial ligand. Quantum dots are dissolved in octane. See Figure 4. When no current is applied, the quantum dots are dispersed in the octane. A voltage is gradually applied to the electrodes starting from 0V. When the voltage increases to a certain level, see Figure 5. The quantum dots start to deposit on the electrodes and form the stripe pattern shown in the figure. The voltage at this point is the driving voltage required for electrodeposition, and indicates to some extent the charge of the quantum dots.
[0072] [Example 2] Core-shell quantum dots CdSe (core) / ZnS (shell) with oleylamine as the initial ligand were mixed with isooctyl alcohol polyoxyethylene phosphate (a phosphate ester surfactant) in a mass ratio of 100:10 and subjected to a ligand exchange reaction to obtain quantum dots with isooctyl alcohol polyoxyethylene phosphate ligands bound to their surfaces. The quantum dots are dissolved in octane, and a voltage is gradually applied to the electrodes starting from 0 V. When the voltage reaches a certain level, the quantum dots begin to deposit on the electrodes, and the voltage at this point becomes the driving voltage required for electrodeposition.
[0073] [Example 3] Core-shell quantum dots CdSe (core) / ZnS (shell) with oleylamine as the initial ligand were mixed with isooctyl alcohol polyoxyethylene phosphate (a phosphate ester surfactant) in a mass ratio of 100:20 and subjected to a ligand exchange reaction to obtain quantum dots with isooctyl alcohol polyoxyethylene phosphate ligands bound to their surfaces. The quantum dots are dissolved in octane, and a voltage is gradually applied to the electrodes starting from 0 V. When the voltage reaches a certain level, the quantum dots begin to deposit on the electrodes, and the voltage at this point becomes the driving voltage required for electrodeposition.
[0074] [Example 4] Core-shell quantum dots CdSe (core) / ZnS (shell) with oleylamine as the initial ligand were mixed with isooctyl alcohol polyoxyethylene phosphate (a phosphate ester surfactant) in a mass ratio of 100:30 and subjected to a ligand exchange reaction to obtain quantum dots with isooctyl alcohol polyoxyethylene phosphate ligands bound to their surfaces. The quantum dots are dissolved in octane, and a voltage is gradually applied to the electrodes starting from 0 V. When the voltage reaches a certain level, the quantum dots begin to deposit on the electrodes, and the voltage at this point becomes the driving voltage required for electrodeposition.
[0075] [Example 5] Core-shell quantum dots CdSe (core) / ZnS (shell) with oleylamine as the initial ligand were mixed with isooctyl alcohol polyoxyethylene phosphate (a phosphate ester surfactant) in a mass ratio of 100:50 and subjected to a ligand exchange reaction to obtain quantum dots with isooctyl alcohol polyoxyethylene phosphate ligands bound to their surfaces. The quantum dots are dissolved in octane, and a voltage is gradually applied to the electrodes starting from 0 V. When the voltage reaches a certain level, the quantum dots begin to deposit on the electrodes, and the voltage at this point becomes the driving voltage required for electrodeposition.
[0076] [Comparative Example 1] Core-shell quantum dots CdSe (core) / ZnS (shell) with oleylamine as the initial ligand are dissolved in octane, and a voltage is gradually applied to the electrodes from 0 V. When the voltage reaches a certain level, the quantum dots begin to deposit on the electrodes, and the voltage at this point becomes the driving voltage required for electrodeposition.
[0077] [Table 1] From Table 1, it can be seen that the driving voltage during electrodeposition can be reduced by modifying the surface of the quantum dots with a surfactant. Furthermore, as the content of the surfactant increases, the driving voltage decreases more rapidly. When the mass ratio of the surfactant to the quantum dots is 1% to 50%, the driving voltage is 50V to 192V. When the mass ratio of the surfactant to the quantum dots is 20% to 50%, the driving voltage may be reduced to 50V to 150V.
[0078] [Example 6] Core-shell quantum dots CdSe (core) / ZnS (shell) with SH-PEG-COOH (mercapto-polyethylene glycol-carboxy) as the initial ligand and isooctyl alcohol polyoxyethylene phosphate were mixed with the polar solvent PGMEA in a mass ratio of 100:1 to obtain a quantum dot solution with isooctyl alcohol polyoxyethylene phosphate ligands bound to the surface. An electrode is immersed in the quantum dot solution and a voltage is gradually applied to the electrode from 0 V. When the voltage reaches a certain level, the quantum dots begin to deposit on the electrode, and the voltage at this point becomes the driving voltage required for electrodeposition.
[0079] [Example 7] Core-shell quantum dots CdSe (core) / ZnS (shell) with SH-PEG-COOH as the initial ligand and isooctyl alcohol polyoxyethylene phosphate were mixed with the polar solvent PGMEA in a mass ratio of 100:10 to obtain a quantum dot solution with isooctyl alcohol polyoxyethylene phosphate ligands bound to the surface. An electrode is immersed in the quantum dot solution and a voltage is gradually applied to the electrode from 0 V. When the voltage reaches a certain level, the quantum dots begin to deposit on the electrode, and the voltage at this point becomes the driving voltage required for electrodeposition.
[0080] [Example 8] Core-shell quantum dots CdSe (core) / ZnS (shell) with SH-PEG-COOH as the initial ligand and isooctyl alcohol polyoxyethylene phosphate were mixed with the polar solvent PGMEA in a mass ratio of 100:20 to obtain a quantum dot solution with isooctyl alcohol polyoxyethylene phosphate ligands bound to the surface. An electrode is immersed in the quantum dot solution and a voltage is gradually applied to the electrode from 0 V. When the voltage reaches a certain level, the quantum dots begin to deposit on the electrode, and the voltage at this point becomes the driving voltage required for electrodeposition.
[0081] [Example 9] Core-shell quantum dots CdSe (core) / ZnS (shell) with SH-PEG-COOH as the initial ligand and isooctyl alcohol polyoxyethylene phosphate were mixed with the polar solvent PGMEA in a mass ratio of 100:30 to obtain a quantum dot solution with isooctyl alcohol polyoxyethylene phosphate ligands bound to the surface. An electrode is immersed in the quantum dot solution and a voltage is gradually applied to the electrode from 0 V. When the voltage reaches a certain level, the quantum dots begin to deposit on the electrode, and the voltage at this point becomes the driving voltage required for electrodeposition.
[0082] [Example 10] Core-shell quantum dots CdSe (core) / ZnS (shell) with SH-PEG-COOH as the initial ligand were mixed with isooctyl alcohol polyoxyethylene phosphate (a phosphate ester surfactant) in a mass ratio of 100:50 with the polar solvent PGMEA to obtain quantum dots with isooctyl alcohol polyoxyethylene phosphate ligands bound to the surface. An electrode is immersed in the quantum dot solution and a voltage is gradually applied to the electrode from 0 V. When the voltage reaches a certain level, the quantum dots begin to deposit on the electrode, and the voltage at this point becomes the driving voltage required for electrodeposition.
[0083] [Comparative Example 2] A core-shell quantum dot solution was obtained by mixing CdSe (core) / ZnS (shell) with SH-PEG-COOH as the initial ligand with the polar solvent PGMEA. An electrode is immersed in the quantum dot solution and a voltage is gradually applied to the electrode from 0 V. When the voltage reaches a certain level, the quantum dots begin to deposit on the electrode, and the voltage at this point becomes the driving voltage required for electrodeposition.
[0084] [Table 2] From Table 2, it can be seen that the driving voltage during electrodeposition can be reduced by modifying the surface of the quantum dots with a surfactant. Furthermore, as the content of the surfactant increases, the driving voltage decreases more quickly. When the mass ratio of the surfactant to the quantum dots is 1% to 50%, the driving voltage is 1V to 48V. When the mass ratio of the surfactant to the quantum dots is 20% to 50%, the driving voltage may be reduced to 1V to 10V.
[0085] The present invention further provides a nanoparticle film, which may be applied in quantum dot display fields such as QDCF (Quantum Dot Color Filter), QD LGP (Quantum Dot Light Guide Plate), QLED (Quantum Dot Light-emitting Diode), QD-OLED (Quantum Dot Organic Light-emitting Diode), and other fields involving other kinds of nanoparticle patterning processes, such as solar cells, spectroscopy, etc.
[0086] The nanoparticle film may be produced by the method for producing a nanoparticle film of the present invention. The nanoparticle film includes nanoparticles having surfactant ligands bonded to the surface. The nanoparticles may be selected from nanoparticles such as nonmetallic inorganic nanoparticles, noble metal nanoparticles, colloidal nanosheets, and colloidal nanorods. If desired, the nanoparticles may be quantum dots. The quantum dot material according to the present invention may be selected from core-shell quantum dots, the light-emitting core may be selected from one of ZnCdSe2, InP, Cd2Sse, CdSe, Cd2SeTe, and InAs, the inorganic protective shell layer may be selected from at least one of CdS, ZnSe, ZnCdS2, ZnS, and ZnO, and the quantum dot material may be selected from highly stable composite quantum dots such as hydrogel-supported quantum dot structures and CdSe-SiO2, or may be perovskite quantum dots. It should be understood that the quantum dot material used in the present invention is not limited to the above.
[0087] The surfactant may be selected from cationic surfactants or anionic surfactants that are easily ionized in a solvent. Specifically, the surfactant may be selected from at least one of organic sulfonate-based surfactants such as calcium dodecylbenzenesulfonate, sodium dodecylbenzenesulfonate, and barium dinonylnaphthalenesulfonate, metal soap-based surfactants such as naphthalene salts and stearates of metals such as cobalt, aluminum, and iron, organic amine-based surfactants such as N-vinylpyrrolidone polymers, and organic phosphate-based and phosphoric acid ester-based surfactants. The surfactant used in the present invention is ionizable in a solvent and has a binding force with the surface of the quantum dots. In order to ensure the binding force between the quantum dots and the surfactant, if desired, a basic surfactant is selected when the surface of the quantum dots is an acidic group, and an acidic surfactant is selected when the surface of the quantum dots is a basic group.
[0088] The quantum dot surface may contain only surfactant ligands, or may contain other ligands, such as oleic acid, thiol, carboxylic acid, and organic amine.
[0089] Optionally, the weight ratio of the surfactant ligand to the nanoparticles is 1% to 50%, or the weight ratio of the surfactant ligand to the nanoparticles is 1% to 5%.
[0090] The nanoparticle film according to the present invention is obtained by electrodeposition at low driving voltages.
[0091] The present invention further provides a display panel comprising the nanoparticle film described above, wherein the nanoparticle film is a quantum dot film.
[0092] Please refer to FIG. 6. The first embodiment of the display panel is a QLED display panel. The quantum dot film 10 is a light-emitting layer of the QLED. Specifically, the display panel 100 includes a first electrode 20, a second electrode 30, and the quantum dot film 10 provided between the first electrode 20 and the second electrode 30. In addition, the display panel 100 may further include film layers such as a hole transport layer, a hole injection layer, an electron transport layer, and an electron injection layer.
[0093] Referring to FIG. 7, the second embodiment of the display panel is an LCD display panel, and the quantum dot film 10 is a color conversion layer of a backlight module of the LCD. Specifically, the display panel 100 includes a liquid crystal cell 40 and a backlight module 50 provided on the non-light-emitting side of the liquid crystal cell 40. The backlight module 50 includes a light source 51, a light guide plate 52, and a quantum dot film 10. The light source 51 is provided on the side of the light guide plate 52. The light source 51 may be a blue light source or a white light source. The quantum dot film 10 is provided between the light guide plate 52 and the liquid crystal cell 40. The quantum dot film 10 is for converting the light incident from the light source 51 to the light guide plate 52 and emitted from the light guide plate 52 into a color required for display, such as green or red.
[0094] Referring to FIG. 8, the third embodiment of the display panel is an LED display panel, and the quantum dot film 10 is a color conversion layer of the LED. Specifically, the display panel 100 includes a light emitting substrate 60 and a color conversion substrate 70 provided corresponding to the light emitting substrate 60. The light emitting substrate 60 is provided with a plurality of light emitting elements (not shown) arranged in a matrix shape, and the light emitting elements may be mini-LEDs or micro-LEDs. The color conversion substrate 70 includes a substrate 71, a color filter layer 72 provided on the side of the substrate 71 facing the light emitting substrate 60, and a quantum dot film 10 provided on the side of the color filter layer 72 facing the light emitting substrate 60. The color filter layer 72 and the quantum dot film 10 can be collectively referred to as a QDCF film.
[0095] The display panel of the present invention utilizes a nanoparticle film and can be manufactured by electrodeposition at a low driving voltage because surfactant ligands are bonded to the surface of the nanoparticle film.
[0096] Although the embodiments of the present invention have been described in detail above, the present specification uses specific examples to describe the principles and embodiments of the present invention, and the above description of the embodiments is merely for the purpose of understanding the present invention. Meanwhile, a person skilled in the art may make changes to the specific embodiments and application scope based on the concept of the present invention, and in summary, the contents of the specification should not be understood as limiting the present invention.
Claims
1. providing a nanoparticle solution comprising a solvent and nanoparticles dispersed in the solvent, the nanoparticles having surfactant ligands attached to their surfaces; forming the nanoparticle solution into a nanoparticle film by electrodeposition; the solvent is a non-polar solvent and the concentration of the surfactant ligand is greater than the critical micelle concentration; The step of providing the nanoparticle solution comprises: Providing an initial nanoparticle having an initial ligand bound to its surface; mixing the initial nanoparticles with a surfactant to effect a ligand exchange reaction to obtain nanoparticles having surfactant ligands bound to their surfaces; and dissolving the nanoparticles having surfactant ligands attached to their surfaces in a solvent to form a nanoparticle solution; The method for producing a nanoparticle film, wherein the surfactant ligand is at least one selected from an organic sulfonate-based surfactant, a metal soap-based surfactant, an organic amine-based surfactant, an N-vinylpyrrolidone polymer, an organic phosphate-based surfactant, and a phosphate ester-based surfactant, and a basic surfactant is selected when the surface of the nanoparticle has an acidic group, and an acidic surfactant is selected when the surface of the nanoparticle has a basic group.
2. 2. The method for producing a nanoparticle film according to claim 1, wherein a mass ratio of the surfactant ligand to the nanoparticles is 1% to 50%.
3. forming the nanoparticle solution into a nanoparticle film by electrodeposition, providing an electrode for immersion in the nanoparticle solution; and applying a driving voltage of 50V to 150V to the electrode so as to deposit the nanoparticle solution on the electrode to form the nanoparticle film.
4. The step of providing the nanoparticle solution comprises:
2. The method of claim 1, further comprising: dissolving initial nanoparticles and the surfactant in a solvent to obtain nanoparticles having surfactant ligands attached to their surfaces, thereby forming a nanoparticle solution.
5. The method for producing a nanoparticle film according to claim 1 , wherein the nanoparticles are quantum dots.
Citation Information
Patent Citations
Light-emitting nanocomposite particles
CN101690401A
Quantum dot solid film and preparation method thereof
CN106479503A
Quantum dot light emitting diode and preparation method thereof
CN111244293A
Dispersion method of nanoscale inorganic particles suitable for composite electrodeposition
CN111809216A
Method of electric field assisted deposition of films of nanoparticles
US20060032755A1